(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Until the onset of the COVID-19 pandemic, one of the seeming givens of therapy for me was that no matter the presenting issue of the client, we could at least agree on the basics, that we were on the same page and watching the same sport. We could agree that the Earth was round and that the sky was blue, and nuanced debate on whether it was hot or cold was welcomed but at least we agreed weather was weather. But since COVID-19 and the extraordinary rise of the conspiracy theory with some clients, all of a sudden we could no longer agree on facts, nuance was lost and discussion became about what and who is right or wrong. Cognitive dissonance was a regular experience and client-therapist relationships that had never been an issue, were frayed. Something had to shift and when I looked into the mirror, the answer was staring back at me.